EUDAIMONIA IN A CUP OF COFFEE: WELL-BEING OF ACEHNESE BARISTA - Akhsani, Yuri; Abidin, Zainal (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2022)
The development of coffee shops in Banda Aceh over the past few years has been accompanied by increasing interest of young people in becoming a barista. This interest is not only caused by the availability of the job, but also the desire to fulfill eudaimonic goals. Based on the concept of eudaimonic well-being, quality of life comes from developing one’s potential and the applications in personally expressive goals, which is shown through the act of pursuing the eudaimonic goals. The phenomenon in Banda Aceh shows that this pursuit comes by becoming a barista. Thus, this study aims to explore the experience of baristas through the framework of eudaimonic well-being theory. This study uses qualitative approach to gain understanding on eudaimonic well-being of baristas in Banda Aceh. The results of this study indicate the pursuit of eudaimonic well-being in all participants, albeit with individually unique methods and motivations.